Software architecture for mobile environments (Revista de Investigaciones Universidad del Quindío, 2014)
The great impact that smartphones are causing currently is due largely to the evolution of their operation systems, which every time are more stable and robust, this allow to the software developers create mobile applications of more size and complexity. The mobile applications have gone beyond of the algorithms and date structure, the specification and design of the general structure of a mobile software system arise as a new kind of problem, and the mobile software architecture as the solution. It research had as goal define a mobile software architecture that will share some of the more important principles of the general software architecture, and so help to standardize and adapt methodologies, process, approaches and others significant contributions to the modern architecture  software to smaller software develop environments. The methodology of investigation used for this project is an adaptation of the Francis Bacon’s scientific method, which is compound of six phases: ask a question, do background research, construct a hypothesis, test your hypothesis by doing an experiment, analyze your data and draw a conclusion and communicate your results. The article is compound of six sections: Introduction, Framework, Methodology, Process for the construction of a mobile software architecture, Results and Conclusions.
Keywords: smartphones; architectural styles; software architecture; mobile software architecture; quality attribute; quality attribute scenarios; screening question